Functional characterization of dopamine transporter in vivo using Drosophila melanogaster behavioral assays - Ueno, Taro; Kume, Kazuhiko (Frontiers in Behavioral Neuroscience, 2014)
Dopamine mediates diverse functions such as motivation, reward, attention, learning/memory and sleep/arousal. Recent studies using model organisms including the fruit fly, have elucidated various physiological functions of dopamine, and identified specific neural circuits for these functions. Flies with mutations in the Drosophila dopamine transporter (dDAT) gene show enhanced dopamine signaling, and short sleep and memory impairment phenotypes. However, understanding the mechanism by which dopamine signaling causes these phenotypes requires an understanding of the dynamics of dopamine release. Here we report the effects of dDAT expression on behavioral traits. We show that dDAT expression in a subset of dopaminergic neurons is sufficient for normal sleep. dDAT expression in other cell types such as Kenyon cells and glial cells can also rescue the short sleep phenotype of dDAT mutants. dDAT mutants also show a down-regulation of the D1-like dopamine receptor dDA1, and this phenotype is rescued when dDAT is expressed in the same cell types in which it rescues sleep. On the other hand, dDAT overexpression in mushroom bodies, which are the target of memory forming dopamine neurons, abolishes olfactory aversive memory. Our data demonstrate that expression of extrasynaptic dopamine transporters can rescue some aspects of dopamine signaling in dopamine transporter mutants. These results provide novel insights into regulatory systems that modulate dopamine signaling.